Analisis Perbedaan Abnormal Return Dan Laba Perusahaan Sebelum Dan Sesudah Share Split Atau Reverse Share Split: Studi pada perusahaan yang terdaftar di Bursa Efek Indonesia periode 2003 – 2010 - Winata, Amelinda Timothea; Suryaningsih, Rosita (Ultimaccounting Jurnal Ilmu Akuntansi, 2012)
The purpose of this research was to analyze the difference of abnormal return and net income before and after share split or reverse share split. Abnormal return and net income are important to investor because it indicated the corporate performance and useful for investor's decision making. The samples used in this research were 61 companies for variable of abnormal return and 59 companies for variable of net income. These samples were the companies that listed in Indonesia Share Exchange (IDX) for period 2003-2010 and meet the criteria sampling of this study. The samples were determined based on purposive sampling method. Data that used in this research was secondary data, such as share price, Indonesia Composite Index (ICI), and financial reports. The method used for analysis was paired sample t-test. The results of this research are (1) there is significant difference between abnormal return before and after share split, (2) there is no significant difference between net income before and after share split, (3) there is significant difference between abnormal return before and after reverse share split, and (4) there is no significant difference between net income before and after reverse share split. Keywords: share split, reverse share split, abnormal return, net income.